2015
DOI: 10.1590/s0100-204x2015000900002
|View full text |Cite
|
Sign up to set email alerts
|

Respostas à seleção de características de desempenho em tilápia-do-nilo

Abstract: Resumo -O objetivo deste trabalho foi estimar parâmetros genéticos e respostas direta e indireta à seleção de características de desempenho em tilápia-do-nilo (Oreochromis niloticus), bem como avaliar o impacto da seleção sobre o ganho genético. Foram utilizadas informações de tilápias-do-nilo, sob seleção em um programa de melhoramento genético, cultivadas em sistema de tanques-rede, de 2008 a 2010. Estimaram-se herdabilidades e correlações genéticas das características ganho em peso diário e, à despesca, pes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
1
4
0
3
Order By: Relevance
“…Works with previous generations, show that participation in the genetic variation of the common environment of larvae production and fingerlings were close to zero, as reported by Oliveira (2011), and lower than reported by Santos (2009) from 0.20 to 0.05 for σ c 2 (common maternal environment = common larvae production environment). The explanation for such high heritability values is that of all of the fish participated in the genetic selection process and the current fifth generation and that the selection criterion is daily weight gain highly correlated with live weight (0.99) (Porto et al 2015). The close estimates of the credibility intervals (ICr) and HPD confirm the symmetrical "a posteriori" distributions (Table III).…”
Section: Resultsmentioning
confidence: 60%
“…Works with previous generations, show that participation in the genetic variation of the common environment of larvae production and fingerlings were close to zero, as reported by Oliveira (2011), and lower than reported by Santos (2009) from 0.20 to 0.05 for σ c 2 (common maternal environment = common larvae production environment). The explanation for such high heritability values is that of all of the fish participated in the genetic selection process and the current fifth generation and that the selection criterion is daily weight gain highly correlated with live weight (0.99) (Porto et al 2015). The close estimates of the credibility intervals (ICr) and HPD confirm the symmetrical "a posteriori" distributions (Table III).…”
Section: Resultsmentioning
confidence: 60%
“…Other researchers (Porto et al, 2015), who evaluated tilapia, also found high association between characteristics, both with genetic information, in which body weight and ADG had a 0.99 correlation and BW association above 0.77, as well as with morphometric information. Oliveira et al (2016) observed that the high association between characteristics are maintained throughout the generations in genetically improved fish.…”
Section: Discussionmentioning
confidence: 76%
“…Além disso, quatro famílias de tambaqui apresentaram ganhos morfométricos (comprimento total, comprimento padrão, comprimento de cabeça, largura e altura corporal) em relação ao grupo controle (MARCOS et al 2016), corroborando com o resultado do nosso estudo, que mostrou que a seleção para peso final pode trazer ganhos nas características morfométricas. Outro estudo com tilápia-do-nilo apresentou resultados que comprovaram que a seleção para ganho de peso diário ocasionou em três gerações ganhos indiretos para largura corporal, 1,11 a 3,08% por geração, altura corporal, 1,23 a 3,48% por geração, e comprimento do tronco, 0,89 a 2,56% por geração (PORTO et al 2015).…”
Section: Discussionunclassified
“…A população melhorada da linhagem GST (GenoMar Supreme Tilapia) obteve ganhos genéticos entre 5% e 15% por geração (ZIMMERMANN 2003). No Brasil, programas de melhoramento de tilápias da linhagem Gift vêm demonstrando ganhos genéticos importantes ao longo de gerações, em diferentes sistemas de cultivo, como o tanque-rede e o viveiro escavado (OLIVEIRA 2011, OLIVEIRA et al 2015, PORTO et al 2015.…”
Section: Introductionunclassified